Detection of single nucleotide polymorphisms in acquired anemia patients with high hemoglobin f - Mohammad, Siti Nur Nabeela A’ifah (2024)
Anemia is a common clinical condition that can be either acquired or inherited. Normally, adults display fetal hemoglobin (HbF) levels of <1%, but variability in genomic regions can cause higher HbF levels (>1%). Unlike inherited anemia, clinical and genetic data on HbF levels associated with acquired causes of anemia among the Malaysian population are still scarce. Therefore, this study aims to determine the association between HbF level and single nucleotide polymorphisms (SNPs) in acquired anemia patients. A total of 106 out of 223 anaemic patients were detected to have high HbF levels using high performance liquid chromatography (HPLC). From 106 patients with high HbF, 79 (74.5%) samples were found to have high HbA2 (=/>3.2%) and were tested with multiplex amplification refractory mutations-system polymerase chain reactions (ARMS-PCR) for β-globin gene mutation while the remaining 27 anemic patients with high HbF has lower HbA2 (<3.2%) were tested using multiplex gap-PCR for four β-globin gene cluster deletion (Siriraj J Gγ(Aγδβ)othalassemia, Thai (δβ)°-thalassaemia, HPFH-6, and Hb Lepore). β-globin gene mutations were detected in 50 patients using multiplex ARMS-PCR, 37 heterozygous Cd26, 6 heterozygous IVS 1-5, 3 heterozygous Cd 41/42, 1 heterozygous IVS 1-1, 2 compound heterozygous Cd26 with Cd8/9, and 1 compound heterozygous Cd26 with Cd41/42. However, no β-globin gene cluster deletion detected in all 27 patients. Besides, there was no significant difference between the HbF levels of acquired and inherited anemic patients. 36 genomic DNA of samples with high HbF and no mutation and deletion together with 5 DNA samples with normal HbF level were chosen for analysis using the Infinium Asian Screening SNPs microarray platform. Two SNPs, rs73170684 and rs2893863 in GSTK1 and CDK1 gene were observed as the most significant variants that achieved GWA significant threshold (p<10-8). However, other SNPs from common major loci associated with high HbF, such as those in HBS1LMYB and BCL11A genes, were not significant. Thus, these findings can be used as a new genetic predictor and guideline for future studies in high HbF levels among acquired anemic patients for better treatment.